Y+4.5=65

Simple and best practice solution for Y+4.5=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+4.5=65 equation:


Simplifying
Y + 4.5 = 65

Reorder the terms:
4.5 + Y = 65

Solving
4.5 + Y = 65

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-4.5' to each side of the equation.
4.5 + -4.5 + Y = 65 + -4.5

Combine like terms: 4.5 + -4.5 = 0.0
0.0 + Y = 65 + -4.5
Y = 65 + -4.5

Combine like terms: 65 + -4.5 = 60.5
Y = 60.5

Simplifying
Y = 60.5

See similar equations:

| c^2-4c+3= | | 36=w-8 | | 27+(-56)+17+33+(-59)= | | 2(2(17))+61= | | 7(-33x-19)=-18(20-5x) | | (-8)(x+6)=0 | | -5(4x-9)+1=-20x+46 | | Y+4.5=6.5 | | 8+35d=-27 | | 9/5k-459.67=105 | | m(m+6n)+7n(m+6n)= | | 9p-72/6p-48 | | 2b+25=75 | | 8(x+d)=3(y-d) | | 3y-9+y+49=6y+40-4y | | 2/3x+6=4(x-11) | | 2(x+8)=18 | | p+17=9 | | 18-4t=22 | | c^2-2c-3= | | 25x+750=1500 | | 7x-3(4-2x)=0 | | 2x+x+2(2x)+61=180 | | 5.5=-16t^2+45t+2.5 | | 27-3x=243 | | -6x+2y=10 | | (4x+8)(5x-15)=0 | | -10+6y=110 | | y=1-ln(x-4) | | q+4=80 | | x^2-11x+21=0 | | 7(x+2)-5= |

Equations solver categories